Community participation and evaluation of mangrove forest rehabilitation activities using multicriteria analysis in Pasar Rawa village, Langkat Regency - O K Hasnanda Syahputra; Mhd. Raihan Fernando (Global Forest Journal, 2024)
Mangrove forests in Pasar Rawa Village have experienced degradation and damage due to activities changing the function of forest areas into oil palm plantations and fish farms. To overcome this, community participation is key in evaluating forest and land rehabilitation (FLR) as a step to restore, preserve, and improve the function and productivity of these forests and land. This research aims to analyze the level of participation and the determination of a set of criteria and indicators for the success of FLR evaluation. This research uses the method scale Likert to determine the level of community participation, and multicriteria analysis is used to choose a set of criteria and indicators for the success of FLR evaluation. This research shows that community participation in planning, implementation, monitoring, and post-planting activities received a high category, and the FLR success rate was 82.3%, including the "good" predicate. This is due to the heightened awareness of the importance of protecting mangrove forests. However, it is still necessary to improve FLR activities in the future so that the mangrove forest in Pasar Rawa village remains sustainable.